2013
DOI: 10.1093/alcalc/agt150
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Vitamins and Brain Dysfunction in Alcoholics

Abstract: Among alcoholics, liver function impairment leads to altered serum vitamin A levels, which are related to brain alterations. Vitamin E levels are also decreased, but although in relation with liver function impairment, its decrease seems to be more dependent on nutritional status and irregular eating habits. Both vitamins are lower in patients with cerebellar atrophy and other features related to brain atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…Recently, it has been reported that serum retinol concentrations are lower in alcoholics 44) and smokers. 45) The decrease in serum retinol concentrations may be one reason why the risk of carcinogenesis is high in people who often smoke and drink.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that serum retinol concentrations are lower in alcoholics 44) and smokers. 45) The decrease in serum retinol concentrations may be one reason why the risk of carcinogenesis is high in people who often smoke and drink.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of SOD reduces the neurotoxicity by amyloid precursor protein and prevents memory deficits by reducing the activity of hippocampal superoxide. The most important exogenous antioxidants in the CNS are vitamin E, C, Omega 3 fatty acids, and selenium but both vitamin E and C levels in the CNS fall after alcohol exposure by ROS activity [121] , [122] .…”
Section: The Potential Therapeutic Approach To Prevent Neurodegenerationmentioning
confidence: 99%
“…Repeated microtrauma associated with the bizarre style of life of many alcoholics, prone to aggression and violence may also contribute ( Harris et al, 2019 ). Altered nutritional status ( Romero-Acevedo et al, 2019 ), or several micronutrient deficiencies also probably play a role ( González-Reimers et al, 2014 ), especially thiamine deficiency ( Topiwala and Ebmeier, 2018 ).…”
Section: Introductionmentioning
confidence: 99%